In-shoe sensor system with an embedded user interface and wearable leg unit - Lourenço, Inês (2020)
In-shoe sensor systems are of great interest to monitor foot health, sports activities and rehabilitation strategies. Among the potential users are people with diabetes, a large part of the population for which monitoring foot pressure and temperature is critical to avoid ulceration, and even amputation. Despite all these reasons the use of foot monitoring devices is still uncommon compared to other accessories such as fitness tracking devices. This work describes the development of an instrumented insole for monitoring pressure, temperature and humidity taking advantage of widely available wearable components. This is made possible by additionally developing a shield board for time-division multiplexing of the pressure signals and an embedded user interface which is stored in the microcontroller's memory and uploaded to a smartphone at start-up via Bluetooth Low Energy. The user interface runs on a smartphone to provide both real time monitoring and averages of sensor data. The system is described in detail and validated by monitoring pressure patterns during stance, by testing response to temperature variations and observing patterns in individuals with pes planus posture.